2013
DOI: 10.3109/10715762.2013.804622
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and APO E polymorphisms in Alzheimer's disease and in mild cognitive impairment

Abstract: A number of evidences indicates oxidative stress as a relevant pathogenic factor in Alzheimer's disease (AD) and mild cognitive impairment (MCI). Considering its recognized major genetic risk factors in AD, apolipoprotein (APO E) has been investigated in several experimental settings regarding its role in the process of reactive oxygen species (ROS) generation. The aim of this work has been to evaluate possible relationships between APO E genotype and plasma levels of selected oxidative stress markers in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…Others: the APO E genotype has been studied in order to correlate genetic risk factors with oxidative stress biomarkers in AD. E4 allele carriers MCI patients have significantly decreased plasma SOD activity compared to non-E4 carriers, with no further difference for other oxidative-stress biomarkers between the two groups [60].…”
mentioning
confidence: 85%
“…Others: the APO E genotype has been studied in order to correlate genetic risk factors with oxidative stress biomarkers in AD. E4 allele carriers MCI patients have significantly decreased plasma SOD activity compared to non-E4 carriers, with no further difference for other oxidative-stress biomarkers between the two groups [60].…”
mentioning
confidence: 85%
“…Using a checkerboard analysis, Lafrenie et al showed that HIV-1 Tat-induced monocyte invasion is inhibited by anti-beta integrin Ab or tissue inhibitor of metalloproteinase (TIMP), indicating an interaction with beta integrins and TIMP (Lafrenie et al 1996a, 1996b; Toschi et al 2001). It is known that apolipoprotein E (ApoE) has neurological implications in Alzheimer’s disease as well as in HIV-infected patients (Chico et al 2013; Sadigh-Eteghad et al 2012; Verghese et al 2013). In the context of HIV, Turchan-Cholewo et al have found that HIV-infected individuals with the E4 allele of ApoE or a history of intravenous drug abuse had increased oxidative stress in the CNS (Turchan-Cholewo et al 2006) while the antioxidant properties of human lipidated apoE3 protects neurons from Tat-induced toxicity (Liu et al 2000; Park et al 2007; Pocernich et al 2004; Turchan-Cholewo et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…While some studies have shown that APOE4 is positively associated with markers of oxidative stress and negatively associated with antioxidant defense markers compared to APOE3 and APOE2 (Chico et al, 2013;Dose et al, 2016). Non significant differences was reported between the APOE isoforms and specific antioxidative properties by Zito et al (2013) and López-Riquelme et al (2016).…”
Section: Introductionmentioning
confidence: 90%
“…In relation to that, it has been reportedthat patients carrying E4 allele are more susceptible to lipid peroxidation. On the other hand, the E2 and E3 isoforms possess greater antioxidant activity (Pulido et al, 2005;Baldeiras et al, 2008;Chico et al, 2013;Dose et al, 2016). Other studies showed that APOE genotype and oxidative stress or antioxidant activities are independent risk factors for dementia (Ihara et al, 2000;Zito et al, 2013;López-Riquelme et al, 2016).…”
Section: Disucssionmentioning
confidence: 99%